Laser machining of WC-Co green compacts for cutting tools manufacturing. (June 2019) - Guimarães, B.; Figueiredo, D.; Fernandes, C.M.; Silva, F.S.; Miranda, G.; Carvalho, O.
Abstract: Nowadays, conventional machining of WC-Co green compacts is used in industries in order to achieve desired dimensions, complex geometries and good surface quality. However, conventional machining presents some problems, namely tool wear, tool breakage, chatter, vibration and deflection besides mechanically induced damage to the compact. Laser machining is a promising approach to machine WC-Co green compacts, since it is performed without contact and allows great flexibility for producing several geometries, high material removal rate, good surface quality and precision, also for complex shapes. It also allows the production of details smaller than 0.2 mm, hardly manufactured by conventional machining, due to the brittle nature of cutting tools of very small dimensions. Due to the abovementioned reasons, laser machining presents a great potential for lowering the production costs of cemented carbide tools. This work addresses the laser machining of WC-Co green compacts, using a Nd:YAG laser and performing different strategies and combinations of laser parameters to obtain different types of profiles (grooves, areas and specific geometries). Results showed that an effective laser machining of WC-Co green compacts is attained when using laser power of 3 W, scan speed of 128 mm/s, 8 passages and line spacing of 0.08 mm. These parameters were effective for obtaining around 800 μm depth geometries, where the addition of a finishing step (1.5 W, 256 mm/s and 8 passages) improved the quality of the edge of the machined geometry. The laser machined compacts were sintered using a SinterHIP process and no undesirable phases were detected, as eta-phase or graphite. Highlights: Laser machining of WC-Co green compacts was successfully performed. Optimum WC-Co laser parameters were: 3 W, 128 mm/s, 0.08 mm spacing and 8 passages. This laser technology does not lead to carbon deficient phases formation. This approach allows creating desired geometries with suitable depths and finishing. Laser machining of green compacts is a viable alternative to conventional machining.